The sign tale of hurst parameter : a revisit - Salleh, Mazleena; Abu Bakar, Ahmad Zaki (2007)

(untitled)
Network traffic measurement studies have shown the presence of self-similar behavior in both local area and wide area traffic traces. In this study we investigated the magnitude of the self-similarity behavior of network traffic and its Hurst measurement, H. Our study has revealed several characteristics of H based on the network traffic changes. From the finding, H can be used as traffic load indicated only if the sampling size is large. On the other hand for a smaller sampling size, H can be used to indicate the change in traffic pattern. However network traffic does not always exhibit self-similarity property. Activities such as peer-to-peer can steer the traffic to lose this property.